1990
DOI: 10.1111/j.1469-8137.1990.tb00427.x
|View full text |Cite
|
Sign up to set email alerts
|

Internal secretory structures in Hypericum (Clusiaceae): H. perforatum L. and H. balearicum L.

Abstract: SUMMARYHypericum species have translucent oil cavities; many species also have superficially similar black internal structures. Contradictory descriptions of both structures emerged from 19th century studies, which we review here. Our study of Hypericum perforatum L. leaves and petals shows typical schizogenous translucent oil cavities that develop with a uniseriate epithelium. Black structures, m contrast, are nodules, each composed ot several large cells lacking a central intercellular space and surrounded b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 9 publications
6
49
0
Order By: Relevance
“…As far as is known, no report is available on the quantification of hypericin or pseudohypericin in the dark glands, although it has been speculated that the dark glands may be the site of accumulation of hypericin or pseudohypericin in H. perforatum plants (McKey, 1979;Curtis and Lersten, 1990;Fornasiero et al, 1998). Moreover, until now, the presence of large numbers of dark glands has been reported only in the petals and leaves (Curtis and Lersten 1990;Fornasiero et al, 1998). In the current study, a significant presence of dark glands (Figs 7 and 8), accompanied by the highest concentrations of Hy-G, has been shown (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As far as is known, no report is available on the quantification of hypericin or pseudohypericin in the dark glands, although it has been speculated that the dark glands may be the site of accumulation of hypericin or pseudohypericin in H. perforatum plants (McKey, 1979;Curtis and Lersten, 1990;Fornasiero et al, 1998). Moreover, until now, the presence of large numbers of dark glands has been reported only in the petals and leaves (Curtis and Lersten 1990;Fornasiero et al, 1998). In the current study, a significant presence of dark glands (Figs 7 and 8), accompanied by the highest concentrations of Hy-G, has been shown (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…14A), it is concluded that long-distance transport of photosynthates via the phloem, xylem or apoplastic space occurs. Dark glands are already known to be connected to the minor veins and vein endings, and are surrounded by an irregular vascular reticulum, which typically includes contact with one or more vein endings (Curtis and Lersten, 1990). Moreover, the dark canals located in different organs (Figs 10 and 11), also known to be associated with veins (Curtis and Lersten, 1990), could be a route of transport as proposed by Williams (1954).…”
Section: P H O T O S Y N T H E S Ismentioning
confidence: 99%
See 3 more Smart Citations